The art of making sh!t up using the principles of improv to become an unstoppable powerhouse - Laviolette, Norm, 1971- (John Wiley & Sons, Inc., 2019)
"Work together to up your chances of business success The Art of Making Sh!t Up combines the lessons learned from a personal journey with the teachings derived from years of honing valuable skills through performing and presenting to thousands of people to demonstrate how working together has helped others found and grow several multimillion-dollar companies. By focusing on topics that serve as pain points and detailing the tools and techniques of improv, this book helps people and organizations utilize new skill sets to be more productive, more accepting, and more "all in" to create a stronger teammate and team. Remove the fear of failure Recognize when and how to trust your instincts Celebrate and embrace the ideas of others Listen effectivelyto both people and your environment Thinking is hard. Listening is easyand is most often the springboard to huge ideas. Find out how it can work for you with The Art of Making Sh!t Up"--